Features of the Development of International Trade in Tourist Services - Obolenska, Tetiana; Yatsenko, Olha; Lyskova, Lesia; Ostian, Zdenek (Dr. Viktor Koval, 2024)
Introduction. The relevance of studying the peculiarities of the development of international trade in tourist services is determined by the significant role of world tourism in the structure of the global economy. In the conditions of a complex international political situation, which is dynamically changing, it is crucial to identify the vectors of the development of the tourism industry to determine the future structure of the macro-regional distribution of tourist flows. Aim and tasks. The purpose of this study is to identify the dominant factors and prospects for the development of international tourism business in the conditions of modern global economic and political instability to determine the most favourable marketing strategies for interaction in the international market of tourist services by extrapolating the results to the possibilities of post-war recovery of the tourism industry in Ukraine. Results. An analysis of international tourism arrivals showed that the average annual growth rate of the industry from 1995 to 2020 average annual growth of international tourist arrivals was more than 4 per cent. Over the estimated period from 1995 to 2023, the average arrival rate decreased to 2.46 per cent. Macro-regions are considered the most promising for the scaling of international tourism, as well as the factors that will contribute to this and can inhibit economic processes. Special attention is paid to the positioning of Ukraine during the post-war recovery of the tourism industry. Forecast indicators indicate that international tourist arrivals to Ukraine could reach 61 million people in the tenth year of the post-war period. An alternative strategy for promoting national tourist products and brands in the target markets of Central and Eastern Europe, Asia, and the Middle East was proposed, and the feasibility of continuing the promotion of Ukraine as a tourist brand was substantiated. Conclusions. This study confirms the vector of the shift in global tourist flows under the influence of a number of factors that deepen the contradictions between the Global South and the North, revealing key trends in the growth and displacement of international tourist flows among countries belonging to two opposite camps. The directions of institutional and structural changes required to restore international tourism in Ukraine in the post-war period to strengthen Ukraine's position in the global tourism market are proposed.